Morphological Diversity of Desmiophyllum Lesquereux Fossil Leaves and Related Palaeoenvironmental Implications from the Early Cretaceous of Northeastern Spain - Luis M. Sender; Josué García-Cobeña; José B. Diez; Alberto Cobos (Diversity)
A variety of leaves of different morphological sizes and venation types corresponding to the gymnosperm genus Desmiophyllum have been found in five fossil sites originating from the Barremian to the Cenomanian periods in northeastern Spain over an interval comprising 25 million years that encompasses the Early Cretaceous–Late Cretaceous boundary. These leaves are preserved in various lithologies corresponding to different depositional environments such as lagoonal systems, coastal swamps, deltaic plains, lacustrine environments and fluvial-related deposits. These new data shed light on the morphological and paleoenvironmental variability of Desmiophyllum recorded in the Cretaceous deposits from southwestern Eurasia.